Current understanding and perioperative management of pediatric pulmonary hypertension. Issue 5 (19th December 2018) - Latham, Gregory J.; Yung, Delphine
Summary: Pediatric pulmonary hypertension is a complex disease with multiple, diverse etiologies affecting the premature neonate to the young adult. Pediatric pulmonary arterial hypertension, whether idiopathic or associated with congenital heart disease, is the most commonly discussed form of pediatric pulmonary hypertension, as it is progressive and lethal. However, neonatal forms of pulmonary hypertension are vastly more frequent, and while most cases are transient, the risk of morbidity and mortality in this group deserves recognition. Pulmonary hypertension due to left heart disease is another subset increasingly recognized as an important cause of pediatric pulmonary hypertension. One aspect of pediatric pulmonary hypertension is very clear: anesthetizing the child with pulmonary hypertension is associated with a significantly heightened risk of morbidity and mortality. It is therefore imperative that anesthesiologists who care for children with pulmonary hypertension have a firm understanding of the pathophysiology of the various forms of pediatric pulmonary hypertension, the impact of anesthesia and sedation in the setting of pulmonary hypertension, and anesthesiologists' role as perioperative experts from preoperative planning to postoperative disposition. This review summarizes the current understanding of pediatric pulmonary hypertension physiology, preoperative risk stratification, anesthetic risk, and intraoperative considerations relevant to the underlying pathophysiology of various forms of pediatric pulmonary hypertension.